New instruments to diagnose acute dyspnoea of cardiogenic origin - Fabrizio Elia; Franco Aprà; Federico Olliveri (Emergency Care Journal, 2008)
Acute dyspnoea is a common symptom in the Emergency Room and differential diagnosis between cardiogenic and primitive pulmonary forms is not always straightforward. The main fundamental elements used for differential diagnosis are medical history and physical examination, plus standard chest x-ray. The advantages and limits of radiological evidence are described, in particular its good specificity but poor sensibility, with a possible absence of congestion signs in up to one third of patients with pulmonary capillary wedge pressure higher than 30 mm H2O. In addition, the radiological differences between cardiogenic pulmonary oedema and ARDS type oedema can be slight and difficult to interpret. Emergency Room physicians can now use new techniques. These are considered and described: BNP or NT pro-BNP biomarker assay and transthoracic ultrasound, evaluated in the light of recent literature. B-type natriuretic peptide (BNP) is produced by myocardiocytes under stress and rises in cases of decompensated heart failure, which is useful in differential diagnosis between cardiogenic and pulmonary dyspnoea. Low values (< 100 for BNP and < 300 for NT pro-BNP) can usually rule out a cardiac origin. High values (> 500 for BNP and > 1000 for Ntpro-BNP), on the contrary, suggest a cardiogenic origin in the absence of septic shock. The limit of this method is the vast grey area of little differential use. Transthoracic ultrasound offers several advantages in that it is relatively easy, quick to learn and conduct and non-invasive. Ultrasound comet-tail images correlate well with interstitial alveolar syndrome and therefore with the presence of extravascular water. Sensitivity and specificity are both high (86.7% and 93%, respectively) in diagnosing alveolar-interstitial syndrome. The technique’s main limit is that the presence of extravascular water does not help differential diagnosis between cardiogenic and injury-related pulmonary oedema. Despite being useful and valid, the new techniques are still inadequate and must therefore be considered a further element of support as part of an integrated evaluation procedure